Peningkatan Keterampilan Menulis Aksara Jawa melalui Model Teams Games Tournament (TGT) pada Peserta Didik Kelas VI SD - Syahputri, Khoirunnisa Noer Azizy; Sayekti, Ika Candra; Tasmun, Tasmun (FONDATIA, 2024)
Javanese script writing skills among students at SDN Kleco 1 Surakarta are still relatively low. This is proven by the percentage of student completion of 43%. This research aims to describe the improvement of Javanese script writing skills through the Teams Games Tournament model for class VIC students at SDN Kleco 1 Surakarta. This research uses the Classroom Action Research method which consists of two cycles. Each cycle has four steps, namely planning, action, observation and reflection. Data collection techniques use observation, tests and documentation. The research instrument uses test questions, observation sheets, and photo documentation. The data analysis technique uses comparative descriptives. Data validity testing was carried out using triangulation techniques. The indicators in this research are based on indicators of writing integrity, clarity of form and neatness of Javanese script. This research was conducted in the VIC class which consisted of 28 students. The research results showed an increase in Javanese script writing skills in the first and second cycles. In terms of the integrity of Javanese script, there was an increase from 72 to 80; clarity of Javanese script forms increased from 81 to 88; and the neatness of Javanese script writing increased from 67 to 78. So it can be concluded that the application of the TGT model can improve Javanese script writing skills. The TGT model in learning can increase students' concentration and involvement, thereby creating fun learning through games.